Mengembangkan Green Job dan Soft Skill: Pengaruh Strategi Pariwisata Berkelanjutan untuk Peningkatan Layanan di Jawa Barat - Muhammad Aziz Winardi; Aldi Friyatna Dira; Kurniawan Prambudi Utomo; Bambang Suntoro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2024)
This research aims to expand developing Green Jobs and Soft Skills: sustainable tourism stategic influence for improving services in West Java. With increasing environmental awareness and the need for sustainable tourism, skill development in the field of green jobs is becoming increasingly significant and necessary. This research method uses quantitative statistics by analyzing this research including surveys and interviews as respondents with tourism workers, entrepreneurs and related stakeholders in several main tourist destinations in West Java and processing the data using SPSS V 25 statistics. The results of the research show that the influence Green jobs and soft skills training are able to improve the quality of tourism services by contributing significantly positively to local economic growth in West Java tourist attractions. The implementation of these influences and strategies is proposed as a holistic and integrated approach to promote sustainable tourism that is economically profitable and environmentally friendly. Keywords: Green Jobs; Tourism; Soft Skills; Service Quality; Economic Growth.